The Role of Quality of Education in Neurocognitive Functioning in a Diverse Sample with Chronic Opioid Use Disorder. (30th August 2019) - Olsen, J; Arnsten, J; Scott, T; Arias, F; Zhang, C; Rivera Mindt, M
Abstract: Objective: Literacy is a proxy for quality of education (QoE) and mediates ethnicity-related differences in neurocognitive (NC) performance in some populations (Manly et al., 2002; Rivera Mindt et al., 2008). However, it is unknown whether this relationship exists in the context of chronic opioid use disorder (OUD). This study examined the role of ethnicity, QoE, opioid use severity, and depression in predicting NC performance in a diverse sample of persons with OUD. Participants and Method: This cross-sectional study included 74 adults with OUD (Age M = 40.3 [SD = 10.5]; Education M = 11.3 [2.5]; 24% female; 68% Latinx and 32% Non-Latinx White [NLW]). All participants completed comprehensive NC testing and psychiatric/substance use questionnaires. Variables included ethnicity (Latinx vs. Non-Latinx White), years of education, QoE (Wide Range Achievement Test, Third Edition; WRAT-3 Reading Standard Scores), opioid use severity (high vs. low OAT dose), current depression (Beck Depression Inventory, Second Edition; BDI-II Total Score), and demographically-corrected NC T-scores were computed and used for average domain T-scores (e.g., learning, memory, verbal fluency, executive function). Bivariate and ANCOVA analyses were used to compare ethnic groups. Results: There were no significant group differences on opioid use severity or current depression (p's > .05). However, compared to the NLW group, the Latinx group had lower years of education (M = 10.9 [SD = 1.7] vs. M = 12.2 [SD = 3.5]; t[72)] = 2.1, p < .05), QoE (M = 83.1 [SD = 13.6] vs. M = 94.8 [SD = 9.4]; t[72] = 3.8, p < .001), executive functioning (M = 42.0 [SD = 6.5] vs. M = 45.8 [SD = 8.5]; t[72) = 2.1, p < .05), and learning (M = 32.2 [SD = 8.2] vs. M = 37.8 [SD = 8.7]; t[72)] = 2.7, p < .05), with medium to large effect sizes (Cohen's d > .50). The overall effect of ethnicity became non-significant for executive functioning after accounting for QoE (F[2, 70] = 10.0, p = .002) and years of education (F[2, 70)] = 16.8, p < .001). Conclusions: The current study found that accounting for years of education and QoE attenuates some differences in NC performance between Latinx and Non-Latinx participants. References: Manly, J. J., Jacobs, D. M., Touradji, P., Small, S. A., & Stern, Y. (2002). Reading level attenuates differences in neuropsychological test performance between African American and White elders.  Journal of the International Neuropsychological Society,   8 (3), 341-348. Mindt, M. R., Arentoft, A., Germano, K. K., D'Aquila, E., Scheiner, D., Pizzirusso, M., ... & Gollan, T. H. (2008). Neuropsychological, cognitive, and theoretical considerations for evaluation of bilingual individuals.  Neuropsychology review,   18 (3), 255-268.